SOFTWARE METHODS FOR INCREASING THE RELIABILITY OF AERODROME QUASI-DOPPLER AUTOMATIC RADIO DIRECTION FINDERS - G. K. Aslanov; R. B. Kazibekov; T. M. Mirzabekov; R. R. Musaibov (Вестник Дагестанского государственного технического университета: Технические науки, 2019)
Objectives To develop software methods that can improve the reliability of airfield quasi-Doppler automatic direction finders (ADFs).Method. Mathematical models and algorithms of software fault recovery of aerodrome quasi-Doppler automatic radio direction finders were developed. It is proposed to change the structure of aerodrome quasi-Doppler automatic radio direction finders.Results. Methods and algorithms for software improvement of the reliability of airfield quasi-Doppler automatic direction finders are proposed. A novel structural organisation of airfield quasi-Doppler automatic radio direction finders is given. New software methods are proposed for ensuring ADF operability in the event of a failure of the antenna system vibrators, both with the use of phase relations from any two pairs of orthogonally arranged ring antenna vibrators and with the use of the combinatorial method. The proposed organisational ADF scheme allows the average operating time per failure of one direction-finding channel to be increased by 4.4 times.Conclusion. The developed methods for ensuring ADF operability in the event of a failure of antenna system vibrators enable a simultaneous calculation of the azimuth and angle of position on the radio emission source. The use of the proposed method increases the potential reliability of airfield quasi-Doppler automatic direction finders without any hardware costs, as well as ensuring the adequacy of the calculated instrumental error values of airfield quasi-Doppler automatic direction finders relative to the real ones.